2008
DOI: 10.1007/s10704-008-9232-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling ductile to brittle fracture transition in steels—micromechanical and physical challenges

Abstract: Both scientists and engineers are very much concerned with the study of ductileto-brittle transition (DBT) in ferritic steels. For historical reasons the Charpy impact test remains widely used in the industry as a quality control tool to determine the DBT temperature. The transition between the two failure modes, i.e. brittle cleavage at low temperature and ductile fracture at the upper shelf occurs also at low loading rate in fracture toughness tests. Recent developments have been made in the understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 113 publications
1
24
0
Order By: Relevance
“…However, in ferritic steels, it has been shown that the misorientation between the ferritic packets was much more important in martensitic steels (such as 21/4 Cr steel) than in bainitic steels (such as A508 steel). These modifications in misorientation distribution between the effective units for cleavage fracture are accompanied by significant improvement in fracture toughness [56].…”
Section: (D) Energy Balance: Number Of Segmentations As a Function Ofmentioning
confidence: 99%
“…However, in ferritic steels, it has been shown that the misorientation between the ferritic packets was much more important in martensitic steels (such as 21/4 Cr steel) than in bainitic steels (such as A508 steel). These modifications in misorientation distribution between the effective units for cleavage fracture are accompanied by significant improvement in fracture toughness [56].…”
Section: (D) Energy Balance: Number Of Segmentations As a Function Ofmentioning
confidence: 99%
“…(20) replaces the exponent of plastic strain in the modified Griffith criterion used previously [2][3][4][5][6][7][8][9][10][11][12][13][14]. As before, it is intended to account for the reduction in crack driving force due to plastic dissipation in the matrix (i.e.…”
Section: Micro-mechanically Informed Modelmentioning
confidence: 99%
“…A different direction of work considers ductile damage prior to cleavage in the DBT regime, employing damage models for the material behaviour coupled with subsequent calculation of failure probability following Beremin [18,19]. This approach has the potential to capture better the fracture behaviour in the DBT, but the models are presently too simplified with no interaction of void growth and micro-cracking at microstructure level [20]. Until advanced coupled models are developed and tested, the wider engineering community would benefit from a simpler uncoupled cleavage fracture model for the DBT region.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] DP microstructure is mainly applied for sheet steels that are thinner than full-size Charpy impact specimens (10 mm Although a few studies on the fracture behavior of dual phase (DP) steels have been conducted, the mechanism of impact fracture in DP steels has not yet been clarified. In this study, the ductile to brittle transition behavior in ferrite + pearlite DP steel sheets was evaluated using the Charpy impact test with a sub-size specimen.…”
Section: Introductionmentioning
confidence: 99%